AR-Math: Augmented Reality–Based Assistive Learning for Enhancing Numeracy Skills Among Students with Intellectual Disabilities - Ferawati, Ferawati; Saputri, Fiqih Hana; Hidayati, Rina (FKIP Universitas Lampung, 2025)
Numerical ability is essential for all students, particularly for those with intellectual disabilities who often face challenges in understanding basic mathematical concepts. This study aims to develop AR-Math, an Augmented Reality (AR)-based learning media designed to improve basic numeracy skills through an inclusive and gender-responsive approach. The development process followed the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. This study employed a quasi-experimental design with a non-equivalent control group design. In this design, there were two groups, namely the experimental class and the control class. The experimental class used AR-Math as the main learning medium, while the control class continued learning with conventional methods. Data were collected using multiple instruments, including validation sheets, practicality questionnaires, pretests and posttests, classroom observation sheets, interview guides, and documentation. The sample consisted of 20 eighth-grade students with mild to moderate intellectual disabilities at SKh YKDW 01 Tangerang, divided into two groups. The results showed that AR-Math met the criteria of validity, practicality, and effectiveness. The effectiveness test revealed a significant improvement in students’ basic numeracy skills, as indicated by a n-gain score of 0.50 and categorized as medium. Beyond cognitive achievement, AR-Math enhanced student engagement, accessibility, and ease of use for students with special needs. A key finding pertains to inclusivity and gender responsiveness. Equal participation between male and female students was observed, as evidenced by comparable levels of interaction, motivation, and task completion during the learning process. This indicates that AR-Math not only strengthens basic numeracy skills but also provides fair opportunities for all learners. Thus, AR-Math can be considered a relevant and innovative tool for inclusive education, supporting both academic development and gender equity in classroom practice. Keywords: assistive, numerical, learning, intellectual, disabilities, augmented reality.